Sistem Informasi Administrasi Pembayaran Hotel Harmony Baturaja Menggunakan Embarcadero XE2 - Julita; Hendrayudi; Dian Sri Agustina (Jurnal Informatika dan Komputer (JIK), 2022)
The research objective was to produce a payment Adminisration Information System that could later be used at Harmony Baturaja Hoteladn with the information system, the outhers hope to be able to assist in data input, payment transportions, and report reporting at the Harmony Baturaja Hotel. In the study the researcher took the Harmony Baturaja Hotel object, with a data collection method that used the research method, Observation and interview, the outhor used 1 (one) Accer laptop unit inside, 2 GB RAM memory, a 500 GB 14 inch hard drive, with the windows 7 operating system and the Embarcadero XE2 application program as well as Xampp 2.5, as for the design of the tables that outhor used were room table,guest table, checkin table, checkout table. At the end of this researcher,the researcher produced an Administrative payments information system at the Hotel Harmony by using Embarcadero XE2 which was designed to help manage employee performance at Harmony Hotels in inputing data,transanction and making reports efficiently.